(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
When starting this work, the authors set out to highlight the most subtle aspects of the classical surgical treatment of congenital inguinal hernias in children, which are often overlooked in the daily activities of a pediatric surgeon. The article outlines the accumulated experience in treating this pathology over the past 7 years and substantiates the need for an individual choice of tactics for managing a child with an inguinal hernia. The points that the authors rely on when choosing an open or endoscopic method of treatment are also given. The problem of training a new generation of pediatric surgeons has been raised in connection with the abolition of classical methods of surgery and the increasing spread and introduction of endoscopy. The evolution of not only the endoscopic method of treatment, but also traditional open hernia repair is shown.